2017
DOI: 10.1587/elex.13.20160955
|View full text |Cite
|
Sign up to set email alerts
|

Novel design of a 2.1–2.9 GHz negative capacitance using a passive non-Foster circuit

Abstract: Non-Foster circuits (NFC), in conjunction with the effect of negative impedance, have been applied to design broadband radio frequencies (RF) due to their wideband impedance matching ability. There are many approaches to designing non-Foster circuits that use transistors with loops inside to obtain negative reactance. Hence, conventional NFC has some problems, including complex connectivity and power consumption. In this paper, we analyse other properties of NFC phase and group delay, and we realize that these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…In Au and Seo (2017), a passive non-Foster capacitance (−5 pF from 2.1 to 2.9 GHz) is reported, implemented as a -network of lumped resistors, inductors and capacitors. A negative inductance of approximately 2 nH in the same frequency range is described (Au and Seo, 2018), implemented as a dispersive transmission line. Without further proof, it can be stated that passive non-Foster implementations are intrinsically narrow band as they rely on frequency dependent, negative group delay networks, as used in the citations mentioned above.…”
Section: Realisation Of Non-foster Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Au and Seo (2017), a passive non-Foster capacitance (−5 pF from 2.1 to 2.9 GHz) is reported, implemented as a -network of lumped resistors, inductors and capacitors. A negative inductance of approximately 2 nH in the same frequency range is described (Au and Seo, 2018), implemented as a dispersive transmission line. Without further proof, it can be stated that passive non-Foster implementations are intrinsically narrow band as they rely on frequency dependent, negative group delay networks, as used in the citations mentioned above.…”
Section: Realisation Of Non-foster Elementsmentioning
confidence: 99%
“…Impedance modulation is used in the uplink direction, while in the downlink, a pulse-width modulated load modulation is employed. Although just achieving a bidirectional data rate of 10 kBit s −1 , a comparable application for biomedical sensors is presented in Chen Gong et al (2017). In contrast to the latter example, frequency division multiplex is employed to transfer the up-and downlink data (binary phase shift keying (BPSK) at 2 MHz centre for energy and uplink data, also BPSK at 125 kHz for downlink data).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the NGD of passive NFC is not as sink as the group delay of a negative group delay network that was presented by Chaudhary [9]. Building on our previous study [6], a new passive NFC structure is proposed as shown in Fig. 2 Fig.…”
Section: Introductionmentioning
confidence: 97%
“…Previous research [6] has mentioned the relationship between phase and group delays of −5 pF. The relationship is applied to design passive NFC that does not have pure phase (phase of ideal negative lump element) and results in more loss than an ideal −5 pF capacitor because of the parasitic resonance and high passive resistor inside the circuit.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, low SA NGD circuits are essential for wireless communication. The NGD circuits have been widely used in practical applications of communication systems, such as shortening or reducing delay lines, enhancing efficiency of feedforward linear amplifier, enhancing bandwidth of feedback amplifier, minimizing beam-squint in phased array antennas systems, realization of non-Foster reactive elements [4,5,6,7,8,9,10,11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%